Use of criteria of quality of life in choice of treatment methods for patientes with malocclusion - J P Mansour (RUDN Journal of Medicine, 2009)
Quality of life in two groups of patients with malocclusion and systemic hypoplasia of enamel was studied. These two groups of individuals received different programs of orthodontic treatment. Comparison of results in two groups revealed the difference between indexes of quality of life in scales of psychological condition, social interaction and aesthetic function.